Analysis of thyroid function and structure and serum metabolomics in pregnant rats exposed to airborne contaminants: Combined perchlorate, thiocyanate, and nitrate exposure - Chenchen Wang; Xiaohui Xu; Jiangling Yuan; Ran An; Aierken Taxitiemuer; Yan Zhang; Tao Luo; Jing Zhou; Chang Wang; Ling Zhang; Shunhua Wu (Ecotoxicology and Environmental Safety)
Objectives: Perchlorates, nitrates, and thiocyanates constitute environmental endocrine disruptors; however, health damage caused by absorption through the respiratory tract remains poorly studied. We investigated the effects of inhalation of these pollutants on thyroid function and structure and serum metabolomics in pregnant rats. Methods: We established a Sprague-Dawley pregnant rat model exposed to perchlorate, nitrate, and thiocyanate at different gestational stages and compared maternal serum thyroid function levels, foetal development, thyroid morphology, and pathological changes between exposed and non-exposed groups at different concentrations. We used liquid chromatography-tandem mass spectrometry metabolomics methods to investigate corresponding changes in serum metabolites and metabolic biomarkers and identify metabolism-related pathways. Results: Free triiodothyronine levels in the medium-and high-concentration groups and free thyroxine levels in the low-, medium-, and high-concentration groups were significantly lower than those in the control group. Weight gain was significantly lower in the high-dose group than in the control group. Thyroid weight and organ coefficients were significantly higher in the medium-and high-dose groups at 15 and 19 days of pregnancy than in the control group. Thyroid epithelial cells demonstrated diffuse proliferation and lamination with increased atomisation concentrations, and thyroid cells tended to undergo apoptosis in the group with high thyroid epithelial cell concentration. Eight and 18 metabolic pathways were significantly affected in the GD15 and GD19 groups（GD15: The demise occurring 15 days into gestation,GD19: The demise occurring 15 days into gestation.）, respectively, post-exposure. The involved pathways included lipid, glucose, bile acid, choline, and gamma-aminobutyric acid metabolism and peroxisome proliferation-activated receptors. Conclusions: Mixed thiocyanate, nitrate, and perchlorate exposure can result in subchronic toxicity in rats, affecting thyroid function and structure.